2023
DOI: 10.47626/2237-6089-2021-0390
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical procedures of the cross-cultural adaptation process of the Child Mania Rating Scale - Parent Version (CMRS-P) for the Brazilian context

Abstract: The initial stages of this manuscript were presented as a research project, in a synthetic way, at the XII Brazilian Congress of Cognitive Therapies ("Cross-cultural adaptation of instruments for the assessment of juvenile (hypo)mania: semantic validation", 2019) and at the 9th Brazilian Congress of Psychological Assessment ("Cross-cultural adaptation of assessment instruments for bipolar disorder in children and adolescents: semantic validation", 2019).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This is the second non-English adaptation of the CMRS, following the Brazilian version published in 2021. 24 The Brazilian version was translated and reviewed by 15 experts and 21 parents/guardians of a representative children/adolescent population. The authors showed a content validity coefficient of 0.95 and an agreement index above 86%.…”
Section: Discussionmentioning
confidence: 99%
“…This is the second non-English adaptation of the CMRS, following the Brazilian version published in 2021. 24 The Brazilian version was translated and reviewed by 15 experts and 21 parents/guardians of a representative children/adolescent population. The authors showed a content validity coefficient of 0.95 and an agreement index above 86%.…”
Section: Discussionmentioning
confidence: 99%